Penyelesaian Sengketa Tanah Overlapping Dengan Cara Mediasi Dihubungkan Dengan Peraturan Menteri Agraria Dan Tata Ruang / Kepala Badan Pertanahan Nasional Republik Indonesia Nomor 21 Tahun 2020 Tentang Penanganan Dan Penyelesaian Kasus Pertanahan: Penyelesaian Sengketa Tanah Overlapping Dengan Cara Mediasi Dihubungkan Dengan Peraturan Menteri Agraria Dan Tata Ruang / Kepala Badan Pertanahan Nasional Republik Indonesia Nomor 21 Tahun 2020 Tentang Penanganan Dan Penyelesaian Kasus Pertanahan - Sugiarto; Hernawati; Juli Asril (Jurnal Media Justitia Nusantara, 2025)
Land is an important resource that often causes conflicts, one of which is overlapping ownership certificates. This conflict leads to legal uncertainty and hinders land utilization. The government, through the National Land Agency (BPN), resolves this issue through peaceful mediation. This study examines how the Bandung City Land Office conducts mediation to resolve disputes arising from overlapping certificates. The research method used is descriptive with a normative juridical approach, collecting data through interviews, observations, and literature review. Qualitative analysis is conducted to understand the mediation process, the cancellation of problematic certificates, and the stages of dispute resolution in accordance with applicable regulations. The results of this study can serve as a reference for developing land mediation systems and assist in formulating policies that ensure legal certainty and protect land rights.